Evaluation of downy mildew resistance in several corn varieties - Gita Pawana; Achmad Amzeri; Ahmad Syaiful Umam; Achmad Djunaedy; Zuli Ika Sulistyowati (Universitas Trunojoyo Madura, 2026)
Peronosclerospora spp. are pathogens causing powdery mildew disease in corn. The increasing number of corn varieties available in the market leads to fluctuations in powdery mildew levels in corn production centres. This study aims to improve the resistance of several corn varieties to powdery mildew by examining stomatal and trichome function and identifying the pathogens involved. This study was conducted in Morosunggingan Village, Peterongan District, Jombang Regency, in October-November 2025, and involved the observation of 0.5 ha of corn plants. Sampling was carried out every 4 days for each variety, starting 4-26 days after planting. The observed parameters analysed included disease incidence, disease severity, AUDPC value, stomatal and trichome density, and the pathogen causing powdery mildew. The conclusions that can be put forward are: 1) Andalan NK007 and Pioneer P40 varieties are more resistant to powdery mildew disease attacks than Berlian 415 varieties. 2) Lower stomatal density and higher trichomes contribute positively to the level of resistance to powdery mildew disease attacks. 3) The powdery mildew disease attack in Morosunggingan Village, Peterongan District, Jombang Regency, was caused by the fungal pathogen Peronosclerospora